2016
DOI: 10.1093/jamia/ocw114
|View full text |Cite
|
Sign up to set email alerts
|

Variation in high-priority drug-drug interaction alerts across institutions and electronic health records

Abstract: Objective: The United States Office of the National Coordinator for Health Information Technology sponsored the development of a “high-priority” list of drug-drug interactions (DDIs) to be used for clinical decision support. We assessed current adoption of this list and current alerting practice for these DDIs with regard to alert implementation (presence or absence of an alert) and display (alert appearance as interruptive or passive).Materials and methods: We conducted evaluations of electronic health record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 28 publications
1
61
1
2
Order By: Relevance
“…Four papers were finally selected as best papers for 2016. Three papers [4][5][6] were selected from PubMed and one paper [7] from WoS in a journal which is not indexed in PubMed. The four papers are listed in Table 1 in the alphabetical order of the first author's surname, and they are discussed in the next section.…”
Section: Review Resultsmentioning
confidence: 99%
“…Four papers were finally selected as best papers for 2016. Three papers [4][5][6] were selected from PubMed and one paper [7] from WoS in a journal which is not indexed in PubMed. The four papers are listed in Table 1 in the alphabetical order of the first author's surname, and they are discussed in the next section.…”
Section: Review Resultsmentioning
confidence: 99%
“…As many as 95% of EMR warnings are overridden, some perhaps appropriately, but many due to alert fatigue . In follow‐up to the publication of high‐priority drug‐drug interaction pairs, an investigation found inconsistent implementation and display of alerts (27%‐93% implementation) . QT‐QT drug interactions were deactivated in 58% of health systems studied.…”
Section: High‐risk Drug‐drug Interaction Alertsmentioning
confidence: 99%
“…47,48 In follow-up to the publication of high-priority drug-drug interaction pairs, an investigation found inconsistent implementation and display of alerts (27%-93% implementation). 49 QT-QT drug interactions were deactivated in 58% of health systems studied. The lack of a standard of care for even high-priority drug-drug interactions is concerning, given that risk is sustained for the duration of concomitant drug administration and for about five half-lives following discontinuation of the interfering medication.…”
Section: High-risk Drug-drug Interaction Alertsmentioning
confidence: 99%
“…These factors may contribute to the greater than 90% override rate consistently reported for clinicians [4]. Moreover, variability across electronic prescribing and pharmacy drug interaction alerting software systems is well-documented and leads to clinician frustration and dissatisfaction [5][6][7][8][9]. A 2017 study of three commercial knowledge bases found substantial variability in the numbers of alerts generated for contraindicated and major/severe PDDIs, with 25, 84, and 145 alerts per 1000 prescriptions for the three systems [10].…”
Section: Introductionmentioning
confidence: 99%